Advanced Process Engineering Control - Agachi, Paul Serban; Cristea, Mircea Vasile; Csavdari, Alexandra Ana; Szilagyi, Botond (De Gruyter Textbook, 2016)
As a mature topic in chemical engineering, the book provides methods, problems and tools used in process control engineering. It discusses: process knowledge, sensor system technology, actuators, communication technology, and logistics, design and construction of control systems and their operation. The knowledge goes beyond the traditional process engineering field by applying the same principles, to biomedical processes, energy production and management of environmental issues. The book explains all the determinations in the "chemical systems" or "process systems", starting from the beginning of the processes, going through the intricate interdependency of the process stages, analyzing the hardware components of a control system and ending with the design of an appropriate control system for a process parameter or a whole process. The book is first addressed to the students and graduates of the departments of Chemical or Process Engineering. Second, to the chemical or process engineers in all industries or research and development centers, because they will notice the resemblance in approach from the system and control point of view, between different fields which might seem far from each other, but share the same control philosophy.